Benson Relaxation Technique for Pain Management in Patients - Nurfadhillah Nurfadhillah; Haeril Amir; Idealriani Idealriani; Erna Marini (PT.Mantaya Idea Batara, 2026)
Background : A fracture is defined as a disruption or loss of bone continuity caused by external forces that exceed the bone's ability to absorb them. Fractures may result from direct impact, crushing forces, sudden twisting movements, or even extreme muscle contractions. Fractures commonly cause pain, which varies among individuals and can affect thoughts, daily activities, and overall quality of life. Effective pain management is therefore crucial, and one of the non-pharmacological interventions that can be applied is the Benson Relaxation Technique. Method : This study used a case study design involving a patient with preoperative radius dextra fracture. The intervention was conducted by applying the Benson Relaxation Technique, in which the patient was guided to sit in a comfortable position, breathe slowly, and repeatedly recite words, phrases, or prayers according to their belief system for 20–30 minutes. Result : The initial assessment at 08:00 revealed that the patient experienced pain with an intensity of 7/10, characterized by facial grimacing, restlessness, and frequently holding the fracture site. After the Benson Relaxation intervention, evaluation at 09:00 showed a reduction in pain intensity to 6/10, and the patient appeared calmer, more relaxed, and less grimacing. Conclusion : The application of the Benson Relaxation Technique proved effective in reducing pain intensity in a preoperative patient with a radius dextra fracture. Before the intervention, the patient reported a pain score of 7, while after the intervention the score decreased to 6. Therefore, the Benson Relaxation Technique can be considered a beneficial non-pharmacological intervention in the management of pain among fracture patients.